Estudio para la creación de una empresa de servicios de consultoría de Comercio Internacional (2021)
The following work proposes a business project that allows to contribute significantly to the growth of companies in the region in terms of consulting in International business, said activity will be focused on the City of Cali, in the department of Valle del Cauca. Companies have been immersed in a constant commercial evolution that energizes the economy. Technological changes and internationalization gives rise to more competitive markets that need allies strategic goals aligned to specific objectives, these goals will be addressed by a team human endowed with the necessary capacities that has the expertise of several years working in the financial sector, oriented to the field of international business. The general objective of this work is to carry out a feasibility study of a company that provides advice so that SMEs in the south west of Colombia can internationalize using exports as an insertion mechanism. To meet With this objective, the feasibility of the market is demonstrated, the aspects technical, legal and administrative, financial aspects are also evaluated, finally, reflect on environmental and social aspects